The Impact of Small Size Firm and Differentiation Strategy in the Niche Strategic Implementation on the Organizational Performance - Maleewat, Nitirat; Banjongprasert, Jantima (Asian Administration and Management Review, 2022)
Niche marketing strategy is a critical strategy applied by many small-size firms to compete with the large-size firms in the same industry. Despite the resource scarcity, small-niche strategy firms differentiate their products or services to address market’s specific needs. Thus, differentiation strategy is one of the significant competitive strategies of small-niche strategy firms to provide high value products or services to the customers, which are different from the rivals. Moreover, communication types and methods may vary from one company to another according to its size. It has many effects on organizational performance. Hence, this study aims to investigate the impacts of the small size of the niche-strategy firms, their differentiation strategy and communication factor of niche-strategy firms on the organizational performance. The quantitative research method is used by distributing the questionnaires to niche-strategy firms in the hospitality industry, Thailand. The data was collected from the sample of 420 employees, who work in hotels, restaurants, travel agent companies and hospitality-related businesses. Structural equation modeling (SEM) was used to analyze the data. The outcome has shown that the small size of the firm, differentiation strategy and communication factor affect the organizational performance of the niche-strategy firms. This study highlights the importance of the key success factors of the firms applying niche strategy to improve their performance.